Fine-structure analysis of the P1 plasmid partition site. - Martin, K A (1991)
P1 plasmid partition requires two plasmid-encoded Par proteins and a cis-acting site. The site, parS, lies in a region consisting of a 13-bp palindrome and an adjacent AT-rich sequence. A series of point mutations were analyzed for their effects on partition site activity. The results indicated that only the left arm of the palindrome and some adjacent bases were needed. The limits of the functional site were further refined to a maximum of 22 bp, which includes binding sites for the P1 ParB protein. Mutations in the 22-bp site cause concomitant defects in partition and the ability to exert partition-mediated incompatibility. Like the region immediately to the left of the 22-bp region, the right arm of the palindrome is not essential for partition but does contain information that affects the specificity of incompatibility.